Cyclical browning in a subtropical lake inferred from diatom records - Emery Boeck, Meredith A.; Gaiser, Evelyn E.; Swain, Hilary M.; Brenner, Mark; Curtis, Jason H.; Kenney, William F. (Frontiers in Ecology and Evolution, 2023)
Changing climate and land use activity are altering inputs of colored dissolved organic carbon (cDOC) into lakes. Increased cDOC reduces water transparency (browning) and changes lake physicochemistry, with biological consequences. Identifying the drivers and effects of changing cDOC inputs is critical for mitigating the consequences of climate change on lake ecosystems through adaptive watershed management. This study focused on determining the drivers of lake browning by evaluating shifts in diatom assemblages in subtropical, oligotrophic Lake Annie (FL, USA), which is known to experience climate-driven oscillations in transparency associated with watershed inputs of cDOC. We combined long-term limnological monitoring data and paleolimnological techniques to determine how diatoms respond to changes in cDOC and to infer past cDOC fluctuations relative to records of past climate and land use changes in the watershed. Diatom assemblage composition in a 14-year phytoplankton dataset was strongly correlated with cDOC-driven transparency fluctuations. Likewise, diatom assemblages in the upper 35 cm of the sediment core, which corresponded to a 35-year lake monitoring record, were also strongly related to past water transparency, yielding a strong transfer function (paleo model, R2 = 0.72). When the model was applied to the diatom record from a 166-cm sediment core, diatom-inferred transparency and rates of nutrient input showed that localized ditching in the 1930s enhanced the effect of climate oscillations on water transparency, intensifying cyclical browning thereafter. Integration of long-term monitoring and paleoecological data provided valuable insights into the history of the aquatic ecosystem, enabling implementation of adaptive management strategies to contend with a changing climate.